The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s13204-018-0650-y
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion resistance of BIS 2062-grade steel coated with nano-metal-oxide mixtures of iron, cerium, and titanium in the marine environment

Abstract: BIS 2062-grade carbon steel is extensively used for fishing boat construction. The steel is highly susceptible to corrosion on the hull and welding joints under marine environment. Here, we demonstrate the application of a novel multifunctional nano-metal-oxide mixture comprised of iron, titanium, and cerium as a marine coating to prevent corrosion. The electrochemical performance of nano-metal-oxide mixture coatings, applied over boat-building steel, was evaluated at 3.5% NaCl medium. The nano-mixture surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Nano metal oxide mixtures of Fe, Ce and Ti were used by Ashraf et al 95 to understand the coating performance on BIS 2062-grade steel which is mainly used for boat construction. They have observed that optimum concentration of nano-mixtures (0.005 % Fe 2 O 3 þ 0.01% CeO 2 þ 0.005% TiO 2 ) are very effective in corrosion protection with a polarisation resistance of $6043 cm 2 and low corrosion current density of 3.53 Â 10 À6 Acm À2 .…”
Section: Came Upmentioning
confidence: 99%
“…Nano metal oxide mixtures of Fe, Ce and Ti were used by Ashraf et al 95 to understand the coating performance on BIS 2062-grade steel which is mainly used for boat construction. They have observed that optimum concentration of nano-mixtures (0.005 % Fe 2 O 3 þ 0.01% CeO 2 þ 0.005% TiO 2 ) are very effective in corrosion protection with a polarisation resistance of $6043 cm 2 and low corrosion current density of 3.53 Â 10 À6 Acm À2 .…”
Section: Came Upmentioning
confidence: 99%
“…Nano mixtures having different properties coated over steel exhibited improved corrosion resistance [16] and few studies have been conducted using the nano materials of different properties in a mixture to prevent biofouling. Nano SiO 2 and ZnO are considered safe, due to their toxicity characteristics and environmental friendliness.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide has commonly been used as additives in anticorrosion coating in the recent years . Nano‐TiO 2 is an excellent cathodic inhibitor, photo‐catalyst, antimicrobial additive and antifouling agent .…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide has commonly been used as additives in anticorrosion coating in the recent years . Nano‐TiO 2 is an excellent cathodic inhibitor, photo‐catalyst, antimicrobial additive and antifouling agent . The TiO 2 NW are semiconductor materials with different properties from a flat titanium alloy surface where a very thin oxide layer is formed only on the surface and the bulk properties remain metallic .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation